The “Solidaritätsprämie” as a missed opportunity? Reasons and remedies for low participation in an Austrian working time reduction policy - Hohner, Astrid; Kaufmann, Raphael; Ulreich, Sidonie; Wich, Tabea (Momentum Quarterly, 2021)
This paper examines the Austrian Solidaritätsprämie, a measure combining working time reduction (WTR) with an active labor market policy (ALMP). Despite its manifold benefits, participation in the Solidaritätsprämie has been relatively low. We seek to shed light on the underlying reasons for this lack of participation and investigate possibilities for the policy’s improvement. Hypotheses are developed on the basis of a comprehensive literature review and five expert interviews are conducted. The data is structured and summarized using framework analysis, allowing for a systematic examination of the hypotheses. We find that participation in the Solidaritätsprämie is thwarted by: (i) absence of direct financial benefits for employers, (ii) firm-specific characteristics, (iii) employees’ reluctance toward WTR, and (iv) lack of information and promotion. Therefore, we propose the following measures to increase participation: (i) financial benefits for employers, (ii) adjustments of the eligibility criteria, and (iii) information and promotion campaigns. Due to the dual character of the Solidaritätsprämie, our findings contribute to a better understanding of WTR and ALMP implementation.
Keywords: working time reduction; active labor market policy; employer participation; Solidaritätsprämie; expert interviews